Biological maturation, contextual factors, and future career in basketball: A possible interrelationship? - Arede, J.; Fernandes, J. F. T.; Freitas, T. T.; Gonzalo-Skok, O.; Leite, N. (Journal of Sports Sciences, 2024)
This study aimed to analyse the relationship between the maturational state and contextual factors with future basketball career success in Under-16 (U16) Portuguese youth preparing for the U16 European Basketball Championships. Eighty-five Under-15 (U15) and U16 male basketball players (height: 189.7 ± 6.53 cm; body mass: 81.1 ± 9.96 kg; the age of peak height velocity: 13.3 ± 0.7 y) were selected by the Portuguese national coaching staff to participate in a national team training camp in 2016, 2017, and 2018 years. A binary logistic regression was employed to identify the influence of maturation, born quartile, demographic, geographic and economic characteristics, and sport career (i.e., drop out during first season and chance of playing professionally). Early maturing players were typically classified as inside players. Training experience and predicted adult height, and type of first club were able to predict players who dropped out during their first season at senior level (both p < 0.01). No variables were able to predict who played in a professional league during their first season at senior level. Practitioners should use these data to consider how national level basketball players are identified and developed, but also keep in mind of their specific contextual factors.